POST-EARTHQUAKE BUILDING DEBRIS MANAGEMENT PLANNING IN CUGENANG SUBDISTRICT, CIANJUR DISTRICT - Stevan Reynardo, Aurey
On Monday, November 21 2022, at around 13.21 WIB, an earthquake measuring 5.6 SR occurred with an epicenter at coordinates 6.84 South Latitude and 107 East Longitude located on land 10 km southwest of Cianjur Regency with a depth of 10 km. This earthquake had a huge impact on one of the sub-districts, namely Cugenang District, where as many as 13,834 houses were heavily damaged, 4,949 houses were moderately damaged, and 4,470 houses were slightly damaged. As a result of this incident, the amount of waste generated in the affected area increased quite a lot. One of them is building debris. Most of the building debris in Cugenang sub-district comes from damaged houses. Therefore, it is necessary to evaluate the building debris waste management system in Cugenang sub-district, Cianjur Regency, and designing a building debris waste management system. It is hoped that the designed facility will be an alternative that will help answer the challenges of managing building rubble waste in areas affected by the Cianjur Earthquake. Currently, building debris after the Cianjur Earthquake is generally only collected and landfilled without further sorting or processing. The planning carried out is to create a building waste processing channel and design a facility for processing building rubble waste that can accommodate the entire capacity of building debris waste generation. The chosen alternative for processing building debris waste after the Cianjur earthquake is by dividing and grouping building debris waste, then processing it using effective technology for processing building debris waste. Meanwhile, waste that cannot be processed is sent to the landfill. The planned construction waste processing facility has an area of 2.800 m². The total investment required is IDR IDR 8,412,364,000. And the total operational costs are IDR 2,438,919,048 per year. By taking into account the Net Present Value (NPV) value, based on the calculation results obtained NPV>0, it can be said that planning to build building debris processing facilities for areas affected by the Cianjur earthquake is economically feasible.